Última parada 174 - Barreto, Bruno; Mantovani, Bráulio; Siaretta, Patrick; Gomes, Michel De Souza; Vianna, Cris; Melo, Marcello, Jr; Luiz, Gabriela; Cotrim, Anna; Lopez, Tay; Zarvos, Marcelo; Héberlé, Antoine; Giffoni, Letícia (Paramount Pictures : AVH [distributor], 2009)
Una crónica de la vida real sobre un secuestro de un autobús en Río de Janeiro que se produjo el 12 de junio de 2000.